2023
DOI: 10.1093/beheco/arad023
|View full text |Cite
|
Sign up to set email alerts
|

Helpers don’t help when it’s hot in a cooperatively breeding bird, the Southern Pied Babbler

Abstract: Cooperative breeding, where more than two individuals invest in rearing a single brood, occurs in many bird species globally and often contributes to improved breeding outcomes. However, high temperatures are associated with poor breeding outcomes in many species, including cooperative species. We used data collected over three austral summer breeding seasons to investigate the contribution that helpers make to daytime incubation in a cooperatively breeding species, the Southern Pied Babbler Turdoides bicolor,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Therefore, relying solely on heat dissipation behaviours may not be sufficient to identify the onset of cognitive decline, and temperature should always be measured alongside behavioural observations. We also found that, despite the occurrence of load-lightening in pied babblers [43], group size did not buffer individuals against temperature-mediated cognitive decline. Indeed, there was no interactive effect of group size and temperature on cognitive performance in associative learning or inhibitory control tasks.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Therefore, relying solely on heat dissipation behaviours may not be sufficient to identify the onset of cognitive decline, and temperature should always be measured alongside behavioural observations. We also found that, despite the occurrence of load-lightening in pied babblers [43], group size did not buffer individuals against temperature-mediated cognitive decline. Indeed, there was no interactive effect of group size and temperature on cognitive performance in associative learning or inhibitory control tasks.…”
Section: Discussionmentioning
confidence: 54%
“…We also found that, despite the occurrence of load-lightening in pied babblers [ 43 ], group size did not buffer individuals against temperature-mediated cognitive decline. Indeed, there was no interactive effect of group size and temperature on cognitive performance in associative learning or inhibitory control tasks.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Like most things in nature, helping is context dependent. Helping may for example be conditional on own failure of reproduction (Hatchwell et al, 2014), the number of other helpers within the group, or environmental conditions (Bourne et al, 2023). In some cooperative breeders, non-breeding individuals provide help simply to not be kicked out or punished by the dominant individuals (Wong et al, 2007).…”
Section: Consequences Of Group Living and Cooperationmentioning
confidence: 99%